The effect of business cycle expectations on the German apprenticeship market : estimating the impact of Covid-19 - Mühlemann, Samuel [Verfasser]; Pfeifer, Harald [Verfasser]; Wittek, Bernhard [Verfasser] (My University, 2020)
"A firm’s expectation about the future business cycle is an important determinant of the decision to train apprentices, especially as German firms typically offer apprenticeships to either fill future skilled worker positions, or as a substitute for other types of labor. The current coronavirus crisis will have a strong and negative impact on the German economy, according to the current business cycle expectations of German firms. To the extent that the training decisions of firms depend on these perceptions, we expect a downward shift in firm demand for apprentices and consequently also a decrease in the equilibrium number of apprenticeship contracts. To assess the impact of changes in business cycle expectations, we analyze German data on the apprenticeship market at the state-level and at the occupation-level within states from 2007 to 2019. We apply first-differences regressions to account for unobserved heterogeneity across states and occupations, allowing us to identify the association between changes in two popular measures of business cycle expectations (the ifo Business Climate Index and the ifo Employment Barometer) and subsequent changes in the demand for apprentices, the number of new apprenticeship contracts, unfilled vacancies and unsuccessful applicants. We find that the German apprenticeship market prior to the current crisis can be characterized by excess demand for apprentices (although there are matching problems in some states, with both a high share of unfilled vacancies and a high share of unsuccessful applicants). Taking into account the most recent data on business cycle expectations up to June 2020, we estimate that the coronavirus-related decrease in firms’ expectations about the business cycle can be associated with a predicted 8% decrease in firm demand for apprentices and a 6% decrease in the number of new apprenticeship positions in Germany compared to 2019 (- 30,000 apprenticeship contracts; 95% confidence interval: +/-8000)." (Authors' abstract, BIBB-Doku)
Keywords: G 1.3.1.1 Ausbildungsstellenmarkt; T 3 Forschungsmethoden; Ausbildungsstellenmarkt; Ausbildungsbereitschaft; Betrieb; Ausbildungsplatzangebot; Einflussfaktor; Pandemie; Infektionskrankheit; Regressionsanalyse; Prognose